1997
DOI: 10.1007/bf02785393
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the effects of selenium on rumen microbial fermentation in vitro

Abstract: The effects of selenium (Se) on ruminant microbial fermentation were investigated in vitro using rumen microflora collected from a rumen-fistulated dairy cow. First, the effects of L-selenomethionine (SeMet; at 0.2 or 2 ppm Se) in the presence or absence of wheat bran (WB, 500 mg per incubation flask) were evaluated. Second, the effects of several forms of Se (elemental Se: 50 ppm Se; sodium selenite: 2 ppm Se; SeMet: 2 ppm Se) were compared. Results showed that the amounts of short-chain fatty acids (SCFAs) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
1
2

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 18 publications
1
18
1
2
Order By: Relevance
“…Fermentação ruminal e absorção de selênio Selenito e selenato podem ser reduzidos a Se elementar (Se 0 ) pelos microrganismos ruminais como um meio de detoxificação (KIM et al, 1997). Os microrganismos podem também incorporar Se na proteína microbiana (HIDIROGLOU & LESSARD, 1976;KIM et al, 1997).…”
Section: Selênio Nos Alimentosunclassified
See 1 more Smart Citation
“…Fermentação ruminal e absorção de selênio Selenito e selenato podem ser reduzidos a Se elementar (Se 0 ) pelos microrganismos ruminais como um meio de detoxificação (KIM et al, 1997). Os microrganismos podem também incorporar Se na proteína microbiana (HIDIROGLOU & LESSARD, 1976;KIM et al, 1997).…”
Section: Selênio Nos Alimentosunclassified
“…Os microrganismos podem também incorporar Se na proteína microbiana (HIDIROGLOU & LESSARD, 1976;KIM et al, 1997). Desse modo, o Se na ração, presente na forma inorgânica, pode ser absorvido no intestino delgado na forma orgânica.…”
Section: Selênio Nos Alimentosunclassified
“…In fact, numerous studies showed that Secompounds affect ruminal microorganism yield and activity of microbiota [1][2][3][4][5][6]. Thus, Se-compounds affect VFAs production and rumen microbial fermentation [5,6].Analyses of the Se content in the ruminal microorganisms revealed that the microbial Se abundance was enriched relatively to the dietary level of Se [7]. Microorganisms are also able to synthesize Se-Met and Se-cysteine (Se-Cys), and these Se-AA are subsequently incorporated into microbial Se-proteins.…”
mentioning
confidence: 99%
“…Se at doses around 0.3 mg Se/kg DM in diet increased (more than by 14%) the molar concentra- Se linear effect 50% grain, P < 0.05, 7 Se quadratic effect 70% grain, P < 0.01, 8 Se quadratic effect 50% grain, P < 0.01, 9 g of microbial nitrogen/kg of OM fermented, 10 nonammonia N leaving the abomasum/N intake tion of butyric acid (Kim et al, 1997;Hernández-Calva et al, 2007). The same way, other authors have reported that the production of acetic, propionic, butyric acids, and total VFA was increased by Se supplementation (Hidiroglou and Lessard, 1976;Wang et al, 2009), and by vitamin E or Se/vitamin E supplementation .…”
Section: Ruminal Fermentationmentioning
confidence: 96%
“…These mi-crobial effects are the cause of the lower absorption of Se in ruminants compared with non-ruminant animals (Serra et al, 1994a). Se availability can affect the in vitro yield of volatile fatty acids (VFA) (Kim et al, 1997) and the in vivo yield of bacterial mass (Serra et al, 1994b), but studies with regard to the effect of Se on nutrient digestibility are few (Serra et al, 1994b;Hernández-Calva et al, 2007). Some effects on microbial activity and digestibility could be observed with a relatively high concentration of Se in the diet.…”
mentioning
confidence: 99%